The role of depressive symptomatology in peri- and post-menopause. Issue 2 (June 2015) - Borkoles, Erika; Reynolds, Nick; Thompson, David R.; Ski, Chantal F.; Stojanovska, Lily; Polman, Remco C.J.
Highlights Peri-menopause associated with higher frequency of depressive symptoms than post-menopause. Menopausal symptoms vary from peri- to post-menopause as an indirect function of depressive symptoms. Depressive symptoms mediates a decline in the frequency of vasomotor and somatic symptoms.